Explicit Evaluations of Cubic and Quartic Theta-Functions. (2012) - Saikia, Nipen
Abstract : We find explicit values of cubic and quartic theta-functions and their quotients by parameterizations. In the process, we also find some transformation formulas of these theta-functions.